2021
DOI: 10.1186/s12874-021-01468-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of limited sample size and follow-up on single event survival extrapolation for health technology assessment: a simulation study

Abstract: Introduction Extrapolation of time-to-event data from clinical trials is commonly used in decision models for health technology assessment (HTA). The objective of this study was to assess performance of standard parametric survival analysis techniques for extrapolation of time-to-event data for a single event from clinical trials with limited data due to small samples or short follow-up. Methods Simulated populations with 50,000 individuals were ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Second, in the dose–response analysis of two prospective cohort studies, although a marginally significant linear association was observed, the exposure levels of Greer's study showed a steady increase in effect sizes, but Honda's study showed a nonlinear association. It is possible that the nonlinear dose–response association of Honda's study was linearized due to the relatively larger sample size of Greer's study 68–70 . The low number of studies included and insufficient data extracted may be other important reasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, in the dose–response analysis of two prospective cohort studies, although a marginally significant linear association was observed, the exposure levels of Greer's study showed a steady increase in effect sizes, but Honda's study showed a nonlinear association. It is possible that the nonlinear dose–response association of Honda's study was linearized due to the relatively larger sample size of Greer's study 68–70 . The low number of studies included and insufficient data extracted may be other important reasons.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the nonlinear dose-response association of Honda's study was linearized due to the relatively larger sample size of Greer's study. [68][69][70] The low number of studies included and insufficient data extracted may be other important reasons. Therefore, further cohort studies with large sample sizes are urgently needed to shed light on the linearity or nonlinearity of the association between sedentary time and MetS risk.…”
Section: Discussionmentioning
confidence: 99%